A classroom observational study of Qatar's independent schools: Instruction and school reform. Issue 4 (3rd July 2016) - Palmer, Douglas J.; Sadiq, Hissa M.; Lynch, Patricia; Parker, Dawn; Viruru, Radhika; Knight, Stephanie; Waxman, Hersh; Alford, Beverly; Brown, Danielle Bairrington; Rollins, Kayla; Stillisano, Jacqueline; Abu-Tineh, Abdullah M. Hamdan; et al.
ABSTRACT: Qatar initiated a K–12 national educational reform in 2001. However, there is limited information on the instructional practices of the teachers in the reform schools. This project was an observational study of classrooms with a stratified random sample of the first six cohorts of reform schools. Specifically, 156 classrooms were observed in 29 reform schools. Instructional differences were noted in schools with different gender of students and were moderated by school level. Implications of findings were discussed pertaining to implementation of the Qatar national reform and professional development needs of teachers.